Conflict Strategies in the Parent–Adult Child Tie: Generation Differences and Implications for Well-Being. (16th May 2017) - Birditt, Kira S; Polenick, Courtney A; Van Bolt, Olga; Kim, Kyungmin; Zarit, Steven H; Fingerman, Karen L
Abstract: Objectives: Irritations often arise in intergenerational ties. Middle-aged individuals report that their relationships with adult children are more important and more negative than ties with aging parents. However, it is unclear whether midlife individuals use different interpersonal conflict strategies with adult children compared to aging parents, and whether the strategies used have implications for psychological well-being. Method: This study examined middle-aged individuals' reports of conflict strategies with their adult children and their aging parents and their own depressive symptoms. Participants were from the Family Exchanges Study; middle-aged adults ( N = 365, ages 45 to 66 years) reported on the conflict strategies used with each of their adult children and their aging parents. Results: Models revealed that middle-aged individuals use more active strategies (e.g., discussing problems) with their adult children than their aging parents. In contrast, individuals used more passive strategies (e.g., avoidance) with aging parents than adult children. Further, passive strategies used with adult children are associated with greater depressive symptoms. Discussion: Findings are consistent with the intraindividual stake hypothesis and imply that conflict strategies used with adult children may be more consequential for psychological well-being than those used with aging parents.